2009
DOI: 10.1128/mcb.01921-08
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor I-C Links Platelet-Derived Growth Factor and Transforming Growth Factor β1 Signaling to Skin Wound Healing Progression

Abstract: Transforming growth factor ␤ (TGF-␤) and platelet-derived growth factor A (PDGF〈) play a central role in tissue morphogenesis and repair, but their interplay remain poorly understood. The nuclear factor I C (NFI-C) transcription factor has been implicated in TGF-␤ signaling, extracellular matrix deposition, and skin appendage pathologies, but a potential role in skin morphogenesis or healing had not been assessed. To evaluate this possibility, we performed a global gene expression analysis in NFI-C ؊/؊ and wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 61 publications
4
55
0
Order By: Relevance
“…Our interpretation of a regulatory interplay between Nfix and cell cycle inhibitors, such as p21, is also supported by a previously described role of Nfix in the regulation of mitogenic pathways in other cell types (Nebl et al, 1994). Our conclusions are also in line with prior observations of regulatory relationships between TGF-b and other Nfi species (Plasari et al, 2009;Plasari et al, 2010) and of BMP7 and Matn2 (Ichikawa et al, 2008) to control the timing of skin-wound healing. In keeping with these findings, we observed severe wound-healing defects in Matn2 2/2 mice on a C57BL/6 genetic background (F. Deák and I.…”
Section: Research Articlesupporting
confidence: 81%
See 2 more Smart Citations
“…Our interpretation of a regulatory interplay between Nfix and cell cycle inhibitors, such as p21, is also supported by a previously described role of Nfix in the regulation of mitogenic pathways in other cell types (Nebl et al, 1994). Our conclusions are also in line with prior observations of regulatory relationships between TGF-b and other Nfi species (Plasari et al, 2009;Plasari et al, 2010) and of BMP7 and Matn2 (Ichikawa et al, 2008) to control the timing of skin-wound healing. In keeping with these findings, we observed severe wound-healing defects in Matn2 2/2 mice on a C57BL/6 genetic background (F. Deák and I.…”
Section: Research Articlesupporting
confidence: 81%
“…Nfi proteins have been implicated in the control of adult stem cells and tissue regeneration in connection with TGF-b signaling (Plasari et al, 2009;Plasari et al, 2010). Nfix has been shown to drive a transcriptional switch from embryonic to fetal myogenesis in vivo and in C2 culture by suppressing the effect of Nfia and activating fetal muscle genes (Messina et al, 2010).…”
Section: Matn2 Is Required For C2 Myoblast Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…These abnormalities have been associated with a decreased proliferation of NFI-C-lacking dental cells due to the overexpression of transforming growth factor ␤1 (TGF-␤1) (8). In addition, we have also shown that NFI-C deficiency affects the normal progression of the skin wound healing process, which has been linked to altered platelet-derived growth factor (PDGF) and TGF-␤ signaling in the knockout animals (9).…”
mentioning
confidence: 81%
“…For instance, PDGF, a potent chemotactic agent for macrophages, is known to activate the growth of telogen follicles (49). We recently found that NFI-C is involved in the inflammatory phase of the skin healing process (9). The PDGF and TGF-␤1 pathways were both found to be affected by the lack of NFI-C, and the increased expressions of PDGF and its receptor ␣ chain were linked to an increased infiltration of macrophages in the skin wounds of knock-out mice.…”
Section: Discussionmentioning
confidence: 99%